Problems of informing of the population about forecasting and appeared extreme situations - Kimstach, И. Ф. (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
In the article the questions connected with informing of the population about emergency situations are stated. The experience of the Russian Federation in the business of elaboration of legislative bases of duly informing of the population and forecasting and appeared emergency situations, maintenance in constant readiness of technical system, and also the appropriate training of the staff of duty and information services of units and divisions on emergency situations is examined.